Container Crane Performance Analysis to Improve Dock Operational Efficiency at PT. Terminal Petikemas Surabaya - Maulana, Ajhar; Sudirman, Sudirman; Akhmad, Ekka Pujo Ariesanto (Universitas Hang Tuah, 2025)
This study analyzes the performance of Container Cranes at PT Terminal Petikemas Surabaya to enhance quay operational efficiency. The main indicators used are Box Crane Hour (BCH) and Box Ship Hour (BSH). Findings show that the 2024 average BSH reached 47.03 boxes/hour (above target), while most cranes did not meet the BCH target of 25 boxes/hour. Key issues include bad weather, equipment downtime, and poor operational coordination. Recommendations include improved maintenance, operator training, and real-time performance monitoring.